Fungal microbiome biodiversity in Larix sibirica Ledeb. needles under biotic and technogenic stress in the Arctic - Miroshnikova, Ksenia A.; Litovka, Yulia A.; Timofeev, Anton A.; Pavlov, Igor N. (Acta Biologica Sibirica, 2025)
Biodiversity plays a crucial role in maintaining the stability of both ecosystems (biocenoses) and individual trees, as it enhances resistance to biotic and abiotic stressors. This study focuses on the phyllosphere fungal communities of Larix sibirica Ledeb. and their role in host resilience under combined stresses from the root pathogen Porodaedalea niemelaei M. Fisch. and technogenic pollution. Samples were collected from four groups of trees: infected with the root pathogenic fungus P. niemelaei, exposed only to technogenic pollution, subjected to both P. niemelaei infection and technogenic pollution, and control trees, which were neither infected nor affected by pollution. DNA was amplified, sequenced, and analyzed using Illumina sequencing technology, yielding 598,891 raw ITS sequences. Varying degrees of larch needle necrosis were observed across the groups, likely influenced by different microbial genera under specific environmental conditions. In samples infected with P. niemelaei, Fusarium and Alternaria dominated, whereas in the group exposed to both P. niemelaei and technogenic pollution, Valsa and Cytospora were the most represented. Notably, the latter group also exhibited a reduced number of unique taxa compared to others, though further studies are needed to confirm statistical significance. The dominant pathogenic genera detected – Fusarium, Alternaria, Valsa, and Cytospora – likely interact with other fungi such as Exobasidium, Ophiognomonia, Sarocladium, Phomopsis, and Taphrina, exacerbating damage and altering the microbiome, particularly under pollution-induced stress.